2020
DOI: 10.20319/pijss.2019.53.215223
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Reliability Between Online and Paper-Based Versions of a Test for Reading in English as a Foreign Language

Abstract: The aim of this study is to examine how reliable the results of the internet-based version of a reading test are, with a view to replacing paper tests with the online versions. This is of increasing importance as universities focus on improving efficiency and supporting SDGs by going paperless.The study was also suggested by the need to test reading comprehension of larger numbers of students across the university and deliver meaningful results on which to base intensive programs of instruction quickly. The Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…This test has been widely used and found to be a reliable measure. The first author has employed both the original EPER paper test and the more recent ERF online test and found that either of the two modes may be reliably used to assess ability (Ihata, 2019). In both groups, test format and procedure for taking the test were explained clearly in advance, both orally in class and in a written handout, and subjects were encouraged to familiarize themselves with the test.…”
Section: Methodsmentioning
confidence: 99%
“…This test has been widely used and found to be a reliable measure. The first author has employed both the original EPER paper test and the more recent ERF online test and found that either of the two modes may be reliably used to assess ability (Ihata, 2019). In both groups, test format and procedure for taking the test were explained clearly in advance, both orally in class and in a written handout, and subjects were encouraged to familiarize themselves with the test.…”
Section: Methodsmentioning
confidence: 99%
“…Some may argue that the lower score obtained might stem from the usage of a computer-based test, instead of a paper-based test. Ihata (2019) mentions that both paper-based and computer or onlinebased tests can be used interchangeably without much problem, and using the online tests is beneficial in reducing the time and cost of a test. However, in order to ascertain that one of the causes for the lower score is not students' unfamiliarity with using a computer, we let students be familiar with how to operate the program and give them time to try out the test using several sample questions.…”
Section: Overall Reading Test's Scorementioning
confidence: 99%